2014
DOI: 10.3928/01477447-20141023-05
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technology in Surgical Education: Combining Real-Time Augmented Reality and Wearable Computing Devices

Abstract: The authors describe the first surgical case adopting the combination of real-time augmented reality and wearable computing devices such as Google Glass (Google Inc, Mountain View, California). A 66-year-old man presented to their institution for a total shoulder replacement after 5 years of progressive right shoulder pain and decreased range of motion. Throughout the surgical procedure, Google Glass was integrated with the Virtual Interactive Presence and Augmented Reality system (University of Alabama at Bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 26 publications
(21 reference statements)
0
77
0
1
Order By: Relevance
“…Studies have reported success in orthopaedic shoulder surgery3 and in training people to acquire simple views during cardiac ultrasonography 4. There are some limitations—a study reported limitations regarding the camera resolution of Google Glass in some scenarios of ECG interpretation 5.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported success in orthopaedic shoulder surgery3 and in training people to acquire simple views during cardiac ultrasonography 4. There are some limitations—a study reported limitations regarding the camera resolution of Google Glass in some scenarios of ECG interpretation 5.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Virtual Interactive Presence and Augmented Reality (VIPAAR) system, developed at the University of Alabama at Birmingham, the local surgeon wore Google glass which allowed the remote surgeon to view the procedure and simultaneously allow the local surgeon to see the virtual interaction from the remote surgeon. 4 The report concluded that the surgery resulted in no complications and illustrates a new and potentially valuable tool in providing additional support for complex procedures and high-risk surgeries. With telemedicine becoming more and more popular, this use of AR shows a promising new development in telemedicine.…”
Section: Patient Care and Potential Applications For Patient Educationmentioning
confidence: 98%
“…Glass has many potential uses within the operative environment including the ability to record a series of videos of operative procedures. The ability to display relevant radiological imaging or other patient monitoring parameters in the surgeon's field of view allows increased situational awareness and focus on core tasks . Glass also opens up the potential use of augmented reality to intraoperatively highlight key pathological/anatomical structures .…”
Section: Potential Applications Of Wearable Technology In Medicinementioning
confidence: 99%